Femoroacetabular impingement surgery: are we moving too fast and too far beyond the evidence?. Issue 12 (12th February 2015) - Reiman, Michael P; Thorborg, Kristian
Abstract : Femoroacetabuler impingement (FAI) is becoming increasingly recognised as a potential pathological entity for individuals with hip pain. Surgery described to correct FAI has risen exponentially in the past 10 years with the use of hip arthroscopy. Unfortunately, the strength of evidence supporting both the examination and treatment of FAI does not appear to accommodate this exponential growth. In fact, the direction currently taken for FAI is similar to previously described paths of other orthopaedic and sports medicine pathologies (eg, shoulder impingement, knee meniscus tear) for which we have learned valuable lessons. The time has come for improved terminology, study design, and focus on delineation of successful treatment variables in the interest of those individuals with clinical indications of FAI so that we can appropriately address their needs.